Energy trading & investing : trading, risk management, and structuring deals in the energy markets - Edwards, Davis W. (New York : McGraw-Hill, 2010)
Energy Trading and Investing provides a highly disciplined and organized approach to profiting from energy investments. This potent combination of detailed, up-to-date information alongside expert know-how thoroughly prepares you to invest and trade with confidence in the energy market. It offers a comprehensive and practical introduction to energy trading- from the big picture of how different products are related to each other to in-depth explanations of the jargon and financial mathematics that trip up new trader.
Includes index.
Series from jacket
nmn 14/05/13
Loans
Keywords: Commodity exchanges; Power resources; Trading - energy markets